Epidemiology and Outcome of Childhood Electrical Burn Injuries at Pakistan Institute of Medical Sciences Islamabad, Pakistan. Issue 2 (March 2016) - Saaiq, Muhammad
Abstract : To describe the epidemiologic profile of children sustaining electrical burn injuries and assess the outcome in terms of need for amputations, hospitalization, and the associated in-hospital mortality. This case series study was performed over a 5-year period (January 2008 to December 2012) at the Department of Plastic surgery and Burn Care Centre, Pakistan Institute of Medical Sciences (PIMS), Islamabad. All children of either gender up to 15 years of age were included. They were admitted for indoor management with standard burn care protocols. The demographic profile of the child, injury characteristics, and outcome were recorded and the data analyzed statistically. Of 85 children who presented with electrical burn injuries during the study period, 89.41% (n = 76) were males and 10.58% (n = 9) were females. The age ranged from 1 to 15 years with a mean age of 10.47 ± 4.09 years. High-voltage burns were the commonest type (n = 61; 71.76%). There were 35 major limb amputations. The mean hospital stay was 6.78 ± 5.01 days (range 1–25 days). The mortality rate was 2.35%. Male children aged 10 to 15 years are the most frequent victims of electric burn injuries, and high-voltage injuries constitute the commonest form of these injuries. There is associated considerable morbidity due to inevitable major amputations of the limbs among otherwise healthy children. There is dire need for primary prevention.